2015
DOI: 10.1016/j.bbr.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of (Val8)GLP-1-Glu-PAL in the MPTP Parkinson’s disease mouse model

Abstract: Glucagon--like peptide 1 (GLP--1) is a hormone and a growth factor. GLP--1 mimetics are currently on the market as treatments for type 2 diabetes. They also have shown neuroprotective properties in animal models of neurodegenerative disorders. In addition, the GLP--1 mimetic exendin--4 has shown protective effects in animal models of Parkinson's disease (PD), and a first clinical trial in PD patients showed promising results.(Val8)GLP--1--glu--PAL is a new GLP--1 analogue which has a longer biological half--li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 45 publications
(51 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, two previous studies showed good protection of MPTP treated mice using the GLP-1 agonist exendin-4 (Kim et al, 2009; Li et al, 2009). We also tested the newer GLP-1 receptor agonists liraglutide, lixisenatide and (Val8)GLP-1gluPAL in this model with good neuroprotective effects (Liu et al, 2015;Zhang et al, 2015). Exendin-4 also has been tested in a pilot study in Parkinson's patients with promising first results (Aviles-Olmos et al, 2013.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, two previous studies showed good protection of MPTP treated mice using the GLP-1 agonist exendin-4 (Kim et al, 2009; Li et al, 2009). We also tested the newer GLP-1 receptor agonists liraglutide, lixisenatide and (Val8)GLP-1gluPAL in this model with good neuroprotective effects (Liu et al, 2015;Zhang et al, 2015). Exendin-4 also has been tested in a pilot study in Parkinson's patients with promising first results (Aviles-Olmos et al, 2013.…”
Section: Discussionmentioning
confidence: 97%
“…The activation of GLP-1 receptors that activate cell growth signaling pathways may be the mechanism by which geniposide exerted the neuroprotective effects in our study. We have previously shown that GLP-1 receptor agonists show neuroprotective effects in the MPTP mouse model (Liu et al, 2015a;Zhang et al, 2015). However, further research in the mechanisms of action of geniposide is required.…”
Section: Discussionmentioning
confidence: 98%
“…Our recent research has demonstrated neuroprotective effects of Val(8)GLP‐1‐GluPal in the MPTP PD mouse model (Zhang et al . ). Oxyntomodulin is a GLP‐1 and glucagon receptor dual agonist (Pocai ).…”
mentioning
confidence: 97%
“…Val(8)GLP-1-GluPal is a new GLP-1 analogue that has longer biological half-life (Lennox et al 2013). Our recent research has demonstrated neuroprotective effects of Val(8)GLP-1-GluPal in the MPTP PD mouse model (Zhang et al 2015). Oxyntomodulin is a GLP-1 and glucagon receptor dual agonist (Pocai 2012).…”
mentioning
confidence: 99%